2017
DOI: 10.1016/j.socscimed.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Gifts and influence: Conflict of interest policies and prescribing of psychotropic medications in the United States

Abstract: The pharmaceutical industry spends roughly 15 billion dollars annually on detailing – providing gifts, information, samples, trips, honoraria and other inducements – to physicians in order to encourage them to prescribe their drugs. In response, several states in the United States adopted policies that restrict detailing. Some states banned gifts from pharmaceutical companies to doctors, other states simply required physicians to disclose the gifts they receive, while most states allowed unrestricted detailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 17 publications
1
40
0
3
Order By: Relevance
“…2,16 Contudo, King e colaboradores (2017) demonstram no seu estudo que, na ausência de presentes, jantares, honorários, canetas, viagens, amostras grátis e outros incentivos, os médicos têm menos probabilidade de prescreverem os novos medicamentos se compararmos com as alternativas já existentes em que os profissionais já possuem mais experiência clínica de uso. 12,17 No trabalho realizado por Redondo e colaboradores (2010), a maioria dos médicos afirma participar de cursos, treinamentos e conferências organizadas pela indústria farmacêutica. Também aceitam convites para almoços e jantares patrocinados pelo laboratório farmacêutico, para reforçar os laços entre médicos e indústria farmacêutica.…”
Section: Resultsunclassified
“…2,16 Contudo, King e colaboradores (2017) demonstram no seu estudo que, na ausência de presentes, jantares, honorários, canetas, viagens, amostras grátis e outros incentivos, os médicos têm menos probabilidade de prescreverem os novos medicamentos se compararmos com as alternativas já existentes em que os profissionais já possuem mais experiência clínica de uso. 12,17 No trabalho realizado por Redondo e colaboradores (2010), a maioria dos médicos afirma participar de cursos, treinamentos e conferências organizadas pela indústria farmacêutica. Também aceitam convites para almoços e jantares patrocinados pelo laboratório farmacêutico, para reforçar os laços entre médicos e indústria farmacêutica.…”
Section: Resultsunclassified
“…Based on a study of doctors' prescriptions in US, it was found that in markets with pharmaceutical product marketing regulations in place, the uptake of new costly medicine was lower; and in states where gifts to doctors were banned, there was a reduction in market share between 39% to 83%. In the absence of gift offerings, peer influence took over as the source of influence (a less biased channel for physicians) when a relatively beneficial drug was introduced in the market (King & Bearman, 2017). As a result of such significant consequences, it can be inferred why pharmaceutical companies do get heavy-handed in the marketing of their products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unethical behaviour has been identified from various literature presented in the last chapter as that behaviour that cannot be defended on legal grounds, is not fair or equitable, or violates another's rights (Buchholz, 1989). In the case of healthcare sector, many researches have shown that accepting gift or any pecuniary benefit that could present a conflict of interest situation with a self-serving bias that could likely result in any stakeholder getting adversely affected fall under the domain of unethical behaviour (King & Bearman, 2017;Moskop et al, 2012;Moynihan, 2009).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…Dort, wo Geschenke an Ärztinnen und Ärzten verboten wurden bzw. eine Pflicht zur Offenlegung eingeführt wurde, wurden weniger Verschreibungen ausgestellt und eine niedrigere Penetrationsrate neuer Medikamente festgestellt (King & Bearman, 2017). Zusammenfassend kann gesagt werden, dass sich die Ziele des Detailing an der Schnittstelle zwischen PR oder Werbung befinden: Genauso viele genuin PR-wie Werbe-Ziele werden dadurch verfolgt (s. Tab.…”
Section: Viorela Danunclassified
“…Aus Sicht der Pharmaunternehmen ist dies notwendig, weil manche Ärzt/innen aus Überzeugung keine Pharmavertreter/innen empfangen. Um dies zu umgehen, rekrutieren Pharmaunternehmen sogenannte key opinion leaders (KOLs) (Lézé & Sidi-Boumedine, 2016;King & Bearman, 2017). Die KOLs charakterisieren sich durch ein hohes Ansehen in der Fachgemeinschaft und ein hohes Verschreibungsverhalten.…”
Section: Pharma-außendienstunclassified